Epidemiology and clinical features of Green pit viper (Trimeresurus trigonocephalus) envenoming in Sri Lanka. (October 2017) - Namal Rathnayaka, R.M.M.K.; Ranathunga, P.E.A.N.; Kularatne, S.A.M.
Abstract: Green pit viper is a venomous endemic snake in Sri Lanka. But little is known regarding its envenoming in the country. This study was carried out in order to find out epidemiology and clinical profile of its bites. A series of 17 patients with Sri Lankan Green pit viper ( Trimeresurus trigonocephalus ) bites was prospectively studied over 4 years. The mean age was 36 ½ years (range 12–61 years) and comprised 14 (82%) males. Except one case, all bites occurred during day time (0600 h-1800 h) due to inadvertent provocation. In 13 cases (76%) bite took place in estates (tea or cinnamon) and 8 patients (47%) were estate workers. The bitten sites were upper limbs in 11 cases (65%) and lower limbs in 6 cases (35%). Ten patients (59%) brought the offending snake to the hospital and one patient was asymptomatic. Sixteen (94%) developed local envenoming features- 16 (94%) local pain and swelling, 6 (35%) local bleeding and lymphadenopathy and blistering in 4 (24%) patients. Systemic envenoming developed in 4 (24%) patients including 3 (18%) with coagulopathy that was treated with fresh frozen plasma. One (6%) patient developed bradycardia. Sri Lankan Green pit viper bites commonly occurs in estates and causes local envenoming frequently and coagulopathy occasionally. Highlights: Study of Sri Lankan Green pit viper ( Trimeresurus trigonocephalus ) bites is presented. First systematic study regarding T. trigonocephalus envenoming in Sri Lanka. Its epidemiology, clinical profile, investigations and treatments are discussed. Morphological features of this endemic species are noted.